The Permanent Revolution? Conservative Law and the Trade Unions - Spencer, Bruce (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "The Permanent Revolution? Conservative Law and the Trade Unions," by John McIlroy.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; Politics & government; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z